Contribution of PKS+ Escherichia coli to colon carcinogenesis through the inhibition of exosomal miR-885-5p - Xiaoming He; Enbo Ren; Lujia Dong; Pengfei Yuan; Jiaxin Zhu; Dechun Liu; Jianguang Wang (Heliyon, 2024)
Objectives: About 90 % of all colorectal cancer (CRC) fatalities are caused by the metastatic spread of primary tumors, which is closely correlated with patient survival and spreads by circulating tumor cells (CTCs). The epithelial-mesenchymal transition (EMT) that characterizes CTCs is associated with a poor prognosis. Organotropic metastasis is dictated by the transmission of miRNAs by cancer-derived exosomes. The purpose of this research is to examine PKS + E's function. Coli in CRC metastases and exosomal miR-885-5p suppression. Methods: A cohort of 100 patients (50 CRC, 50 healthy) underwent colonoscopy screenings from February 2018 to August 2021. Exosomes were isolated using ultracentrifugation, and exosomal miRNA was analyzed using sequencing and qPCR. Results: Among the patients, 40 tested positive for E. coli (12 CRC, 23 healthy). Serotyping revealed that 68.57 % harbored the PKS gene. Exosomal miR-885-5p levels were significantly altered in CRC patients with PKS + E. coli. Intriguingly, our findings indicate that exosomes derived from EMT-CRC cells did not affect miR-885-5p synthesis in HUVECs. Moreover, we observed that the levels of miR-885-5p in both exosomes and the total CRC-conditioned medium were comparable upon isolation of exosomes from CRC cells. What's more, an increased expression of miR-558-5p within the tumors, and the group that received exosome treatment, as well as the EMT-HCT116 group, exhibited a higher occurrence of distant metastasis. Conclusion: PKS + E. By inhibiting exosomal miR-885-5p, coli is linked to CRC metastases, offering a possible target for therapeutic intervention.